An innovative piston corer for large‐volume sediment samples. (13th July 2016) - Gallmetzer, Ivo; Haselmair, Alexandra; Stachowitsch, Michael; Zuschin, Martin
Abstract: Coring is one of several standard procedures to extract sediments and their faunas from open marine, estuarine, and limnic environments. Achieving sufficiently deep penetration, obtaining large sediment volumes in single deployments, and avoiding sediment loss upon retrieval remain problematic. We developed a piston corer with a diameter of 16 cm that enables penetration down to 1.5 m in a broad range of soft bottom types, yields sufficient material for multiple analyses, and prevents sediment loss due to a specially designed hydraulic core catcher. A novel extrusion system enables very precise slicing and preserves the original sediment stratification by keeping the liners upright. The corer has moderate purchase costs and a robust and simple design that allows for a deployment from relatively small vessels as available at most marine science institutions. It can easily be operated by two to three researchers rather than by specially trained technicians. In the northern Adriatic Sea, the corer successfully extracted more than 50 cores from a range of fine mud to coarse sand, at water depths from three to 45 m. The initial evaluation of the cores demonstrated their usefulness for fauna sequences along with heavy metal, nutrient and pollutant analyses. Their length is particularly suited for historical ecological work requiring sedimentary and faunal sequences to reconstruct benthic communities over the last millennia.